DGI-012 Antibiotics Monitoring: The Experience of Liguria Region, Italy. (12th March 2013) - Nurchis, C; Chiarello, T; Bianchi, C; Ferelli, E; Morotti, F; Gamba, S; Riceputi, L; Brega, A; Trovato, F; Zuccarelli, S; Borgna, S; Peri, S
Abstract : Background: The Health Department of Regione Liguria has introduced the obligation, for every hospital department to motivate the request to obtain certain kinds of antibiotics, because their use is restricted to serious infections and in consideration of their high cost. Purpose: The aim is to restrict the phenomenon of resistance to antibiotics and reduce the rising consumption of these drugs, guaranteeing a correct prescription. Materials and Methods: The request for the drugs in question must be made using the appropriate form containing the clinical data of the patients, including personal details, diagnosis and the characteristics of the infection. The pharmacist verifies the administration dosage and the conformity of the diagnosis with the approved health authority indications and with prophylaxis guidelines. The pharmacist will then decide whether to dispense the drug. Some hospitals make use of written applications, others have created specific software for this purpose, others have included the application in the software for the management of the hospital admissions and patients records. Furthermore, where necessary, it has been possible also to include specialist advice, in the software. Results: In the 2011 the Local Health Board of Genoa (ASL3) received and monitored 2274 specific forms, that is 100% of the requests. The intervention of the pharmacist led to a reduction of 90% in the use of Tigecycline and prevented, in 31 cases, an overdose of Vancomycin hydrochloride on Clostridium Difficile Infection. Administration of oral vancomycin in Clostridium difficile infection was 500 mg qid orally for at least 10 days instead of 125 mg qid orally stated in the international guidelines. The control of reasoned request by the pharmacist allowed to use the appropriate dosage. In the Galliera Hospital, 2100 specific forms were filled out (70% of the total requests). Antibiotics non requiring a specific request like ciprofloxacin, ceftriaxone, ceftazidime were used more than in 2009. (2009: 20872units; 2011:25508 units) The Local Health Board of Chiavari (ASL4) received 1525 applications (59% on-line). Conclusions: This method has led to an increase in appropriate prescriptions and to better collaboration among medical staff. No conflict of interest.